Kitab Kuning and Javanese Language Maintenance in Pondok Pesantren Al-Falah Salafi Brebes - Mohammad Andi Hakim; Fifi Novianty (The Institute of Research and Service Community IPMAFA Pati, 2020)
This study reveals the role of Pesantren and Kitab Kuning in maintaining Javanese Language. This focus on how the Javanese language maintenance process through the transmission of cultural values ​​and learning at the Pesantren Al-Falah Salafi Brebes and other supporting factors of the Javanese language maintenance process. This qualitative research uses a sociolinguistic approach. The type of data is the form of socio-cultural words and expressions, learning curricula, and Javanese language maintenance programs in Pesantren. Data collection techniques used were interviews, observation and document study. Data analysis technique is done by identifying, classifying and interpreting the data. The results showed that the process of maintaining Javanese language takes place on several ways: 1) Learning Kitab Kuning through Sorogan, Bandongan, Pasaran methods. 2) Tradition of dialogue through Khitobahan, Majlis Orda and Bahtsul Masail. 3) Personification of Kiai with the necessity to use Javanese language, and 4) Formal and informal communication. All these activities make Javanese language be maintained in Pesantren.